Childhood psychological maltreatment subtypes and depression among Chinese college students: the role of self-compassion and perceived negative attention bias - Yufei Xie; Xin Tian; Xici Wan; Yuting Zhang; Ying Guo (BMC Psychology)
Abstract Background Research on childhood psychological maltreatment lags behind that on other forms of childhood maltreatment. While it has been identified as a significant predictor of depression, the specific underlying mechanisms linking its subtypes (emotional abuse and emotional neglect) to depression remain unclear. This study aimed to examine the association between childhood psychological maltreatment and its subtypes and depression from both emotional factors (self-compassion) and cognitive factors (perceived negative attention bias), as well as the gender differences. Methods Using a questionnaire survey, a total of 587 college students completed the self-report questionnaires, including childhood psychological maltreatment and its subtypes, self-compassion, perceived negative attention bias, and depression. This study used structural equation models to examine the serial mediating role and gender differences by Amos 24.0. Results Childhood psychological maltreatment and its subtypes positively predicted depression. Self-compassion played a mediating role between childhood psychological maltreatment and its subtypes and depression. Perceived negative attention bias played a mediating role between childhood psychological maltreatment and emotional abuse and depression, but not significantly between emotional neglect and depression. Self-compassion and perceived negative attention bias played a serial mediating role between childhood psychological maltreatment (including its subtypes) and depression. There were no gender differences in the mediating role. Conclusion Self-compassion and perceived negative attention bias played distinct roles in the association between childhood psychological maltreatment, its subtypes, and depression. A serial mediating role of self-compassion and perceived negative attention bias was observed in the associations between overall psychological maltreatment, emotional abuse, and depression. In contrast, in the case of emotional neglect, only self-compassion served as a mediator. These findings enlighten us that psychological interventions enhancing self-compassion and reducing negative attention bias may help mitigate depression in college students exposed to childhood psychological maltreatment, particularly emotional abuse. Conversely, interventions focused on increasing self-compassion may be more effective in reducing depression in those exposed to emotional neglect.